A study of clinical profile of intractable epilepsy in children - Sree, C. Bhanu; Belavadi, Gangadhar B. (International Journal of Contemporary Pediatrics, 2020)
Background: This study was undertaken to find out the prevalence and clinical features of intractable epilepsy (IE) in a tertiary referral center. Methods: Study was conducted in a tertiary care hospital on 60 children with intractable epilepsy. Cases includes intractable epilepsy is when seizures continue to occur despite maximally tolerated doses of more than two antiepileptics, occurrence of an average of one seizure per month for 18 months with no more than a 3 month seizure free period during these 18 months. Controls: epileptic children who had good control of seizures for the previous 18 months. Results: The prevalence of intractable seizures was 10% with maximum number of children 25 (41.6%) belonged to the 5-12 years. 15 (50%) children had daily seizures. Myoclonic seizures proved to be an important predictor of intractability. 4 children among the cases had history of family seizures, 6 children in cases had history febrile seizure, whereas, 6 children among the controls had history of family seizures, 8 children in controls had history febrile seizure. 23.3% of children presented with Status epilepticus in the cases and 16.6% of the children in the controls. Remote symptomatic etiology 12(40%) is the commonest cause of seizure. 13 (43.3%) children in cases and 3 (10%) children among the controls had a history suggestive of birth asphyxia. EEG was abnormal in 17 (56.6%) cases when compared to 11 (36.6%) children in the controls. CT scan was abnormal in 14 (46.6%) cases and 10 (33.3%) controls. MRI was abnormal in 16 (53.3%) children of the cases and 8 (26.6%) children of the controls. Conclusions: The commonest cause of intractable epilepsy was perinatal asphyxia. Perinatal asphyxia can be prevented by good nutrition during pregnancy, regular antenatal check ups with detection of high risk pregnancy, promoting hospital deliveries and prompt resuscitation of newborn when required.